Evaluation of Oxidative Stress-related Biochemical Parameters in Experimentally Induced Hepatotoxicity by Lantana camara in Female Wistar Rats and its Amelioration with Neem (Azadirachta indica) Leaf Extract - Meena, Naresh; Purohit, K.; Singh, G.; Rathore, A.; Solanki, S.; Chavhan, M. D.; Kumari, M.; Yadav, B.; Mamta; Kumar, K. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during August, 2024 to January, 2025 at College of Veterinary and Animal Science, Navania Vallabhnagar, Udaipur, Rajasthan, India to evaluate oxidative stress-related biochemical parameters in female Wistar rats subjected to Lantana camara induced hepatotoxicity, and to assess the hepatoprotective effects of Azadirachta indica (Neem) leaf extract against the induced toxicity. Five experimental groups were established. Group I served as the control, Group II received only Neem extract, and Group III was administered Lantana camara to induce hepatotoxicity. Group IV was pre-treated with Neem extract for 10 days prior to Lantana camara exposure, while Group V received Neem extract following Lantana camara–induced hepatotoxicity (post-treatment group). Biochemical markers, including lipid peroxidation (LPO), superoxide dismutase (SOD), glutathione reductase (GR), and catalase (CAT), were measured to assess oxidative stress and antioxidant defense mechanisms. The results showed that Lantana camara significantly increased oxidative stress, as evidenced by elevated LPO levels and decreased antioxidant enzyme activities. The study also revealed that L. camara induced significant hepatic damage mediated through oxidative stress, while neem leaf extract provided hepatoprotection by restoring antioxidant enzyme levels and preserving liver histoarchitecture.